(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Security and Privacy protection have been a public approach worry for quite a long time. Notwithstanding, quick innovative changes, the fast development of the internet and electronic business, and the improvement of more modern techniques for gathering, investigating, and utilizing individual information have made privacy a significant public and government issues. The field of data mining is acquiring importance acknowledgment to the accessibility of a lot of data, effortlessly gathered and put away through PC systems. Data mining procedures, while permitting the people to remove shrouded information on one hand, present various privacy dangers then again. In this paper, we concentrate a portion of these issues alongside an itemized conversation on the utilizations of different data mining strategies for giving security. This paper gives an outline of data mining field and security information event management system. We will perceive how different data